2022
DOI: 10.14701/ahbps.21-094
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in inflammatory markers predict hepatocellular carcinoma recurrence and survival after liver transplantation?

Abstract: The role of inflammation in malignant cell proliferation has been well described. High values of platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) as markers of systemic inflammation have shown associations with unfavorable long-term outcomes. The purpose of this study was to determine values of NLR and PLR evaluated prior to and after surgery and their associations with mortality and recurrence rates of liver transplant patients with hepatocellular carcinoma (HCC). Methods: A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…According to VIMP analysis, PNLR and PLR were two important risk factors for the recurrence of huge HCC. According to previous studies, PNLR or PLR can be used as clinical indicators of the host inflammatory response and immune status, while an increasing PNLR or PLR is a strong predictor of poor survival in certain types of malignancies (47)(48)(49)(50). It has been reported that a higher PNLR and PLR were correlated with a poorer prognosis among patients with HCC (48).…”
Section: Discussionmentioning
confidence: 99%
“…According to VIMP analysis, PNLR and PLR were two important risk factors for the recurrence of huge HCC. According to previous studies, PNLR or PLR can be used as clinical indicators of the host inflammatory response and immune status, while an increasing PNLR or PLR is a strong predictor of poor survival in certain types of malignancies (47)(48)(49)(50). It has been reported that a higher PNLR and PLR were correlated with a poorer prognosis among patients with HCC (48).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years several authors reported a strong correlation between systemic inflammation and HCC prognosis with different systemic and pathological markers associated with survival and recurrence. For example, high values of platelet-tolymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR) and other similar scores seem to predict poor long-term outcomes after treatment (9)(10)(11). This relationship is also evident on a molecular level as gene expression alterations are at the basis of these inflammatory cell shifts on which cancer develops and progresses (12).…”
mentioning
confidence: 99%